1991
DOI: 10.1364/ao.30.004034
|View full text |Cite
|
Sign up to set email alerts
|

Dual-beam interferometer for the accurate determination of surface-wave velocity

Abstract: A novel dual-beam interferometer has been designed and constructed that enables two beams from a He-Ne laser to probe remotely the surface of a material. The separation of the two He-Ne beams is adjustable in the 15-to- 40-mm range with a spatial resolution of 2 microm. Surface-acoustic-wave measurements have been performed with two different probe separations so that the travel time for the surface waves over a known distance can be determined accurately. With the aid of autocorrelation algorithms, the Raylei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…With this approach the advantages of laser generation are maintained, in particular the capability of generating acoustic waves in a wide frequency range without any contact, while there is no loss in sensitivity in the detection side. An optical interferometer, kindly loaned to us by Dr. Mignogna of the Naval Research Laboratory, was initially used to characterize our experimental setup [6]. Unfortunately, it was not possible to utilize the optical detection for studying the specimen of interest, and it was found that piezoelectric transducers were adequate.…”
Section: Introductionmentioning
confidence: 99%
“…With this approach the advantages of laser generation are maintained, in particular the capability of generating acoustic waves in a wide frequency range without any contact, while there is no loss in sensitivity in the detection side. An optical interferometer, kindly loaned to us by Dr. Mignogna of the Naval Research Laboratory, was initially used to characterize our experimental setup [6]. Unfortunately, it was not possible to utilize the optical detection for studying the specimen of interest, and it was found that piezoelectric transducers were adequate.…”
Section: Introductionmentioning
confidence: 99%
“…Dual-probe displacement-measuring laser interferometers [1][2][3][4][5][6][7] simultaneously measure the motion of a reflective object at two different spatial locations. Most commonly, they are used as contactless receivers of ultrasound, especially for the accurate determination of the propagation velocity and attenuation of surface acoustic waves.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the employed detection technique, they can be classified as either heterodyne [1,3,7] phase detection laser interferometers or homodyne [2,[4][5][6] amplitude detection laser interferometers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing dual-probe interferometer designs either use the reference beam and the object beam as the two individual probes to make a differential measurement, [2][3][4][5] or simply combine the components of two ͑independent͒ single-probe interferometers. 6 The multimode and dispersive nature of Lamb waves complicates their interrogation with a differential measurement system; since a time-domain Lamb wave signal is relatively long, the ͑optical͒ signals from the ͑coupled͒ reference and object beams can interfere with each other, causing spurious results in the Lamb wave signal.…”
Section: Introductionmentioning
confidence: 99%